CORRELATION BETWEEN DIETARY HABBITS WITH SEVERITY OF DYSMENORRHEA AMONG ALDOLESCENT GIRL - Arvelina Novia Damayanti; Bagus Setyoboedi; Widati Fatmaningrum (Indonesian Midwifery and Health Sciences Journal, 2022)
Abstract Introduction: More than 50% of women in each country on the world have dysmenorrhea. Dysmenorrhea can disturbing daily activities ,reduces the quality of life and learning activity indeed absent from school for a few hours or days. The purpose of this study is to determine corelation between diet and the severity of dysmenorrhea in SMK Negeri 2 Lumajang. Method: This study used observational analytic study design with a cross-sectional approach. The population was all female student in SMK Negeri 2 Lumajang. Total sample are 89 students calculated with Slovin formula. Used questionnaire as a instrument. Analysis of this study using chi square test. Result: Most of the respondents had good fat intake, while intake of Ca and Fe was less, frequency of eating 2x/day, total of bad intakes was 2, frequency of eating 2x/day, and severity of dysmenorrhea is severe dysmenorrhea . results of the chi square analysis of fat towards severity of dysmenorrhoea got p = 0.001, on fe, ca and the amount of intake that did not match towards severity of dysmenorrhoea, p = 0.000 and on the frequency of dysmenorrhea towars severity of dysmenorrhea, p = 0.773. Conclusion : there is a corelation between dietary habbit according to intake of fat, Fe, Ca, total bad intake with the severity of dysmenorrhea. And there is no corelation between dietary habbit according to eating frequency with the severity of dysmenorrhea.